Pharmacotherapy in allergy medicine: from 'ipse dixit' to the evidence-based medicine. Issue 4 (August 2020) - Mennini, Maurizio; Arasi, Stefania; Dahdah, Lamia; Pecora, Valentina; Fiocchi, Alessandro
Abstract : Purpose of review: The aim of the article is to examine the contributions made in recent years by evidence-based medicine to the understanding, positioning, and use of drugs for the treatment of the main allergic conditions. Recent findings: Several antiasthmatic drugs have been reappraised for their efficacy characteristics and drug interactions in Cochrane reviews. The Allergic Rhinitis and its Impact on Asthma (ARIA) guidelines have been reformulated in evidence-based medicine (EBM) terms in 2017; over these years, new point of care instruments contributed to the approximation of the guidelines to real life by drawing from the patients themselves information that allows to finely modeling the pharmacological suggestions. Last, at the time of the emergence of new drugs for the treatment of peanut allergy, new systematic reviews have helped to focus on the most suitable reference outcomes with the aim to respond promptly and adherently to patients' needs. Summary: EBM has contributed to changes in the GINA guidelines in the last two years. It has been instrumental in translating the ARIA guidelines in real life. It has also contributed to profiling the potential and limitations of oral peanut immunotherapy. In allergy medicine, EBM is a formidable aid for the advancement of knowledge.